2008 58th Electronic Components and Technology Conference 2008
DOI: 10.1109/ectc.2008.4550279
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of underpad stress in thermosonic copper ball bonding

Abstract: Ball bonding processes on test chips with Al metallized bonding pads are optimized with one Au and two Cu wire types, all 25 µm diameter, obtaining average shear strengths of more than 120 MPa. The process temperature is about 110 °C. The results demonstrate that ball bonds made with Cu wire show at least 15% higher shear strength than those made with Au wire. The estimated maximum shear strength c pk value determined for Cu ball bonding (c pk = 3.7 ± 1.2) is almost 1.5 times as large than that of the Au ball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Electronic devices with high‐circuitry integration of IC chips require high I/O numbers for power, thermal and signal management, and thus the BPPs must be reduced (Goh and Zhong, 2007b). The demand for reducing manufacturing costs and improving performance is also driving low‐cost packaging for fine pitch and high I/O devices (Shah et al , 2008).…”
Section: The Benefits Of Fine and Ultra‐fine Pitch Wire Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic devices with high‐circuitry integration of IC chips require high I/O numbers for power, thermal and signal management, and thus the BPPs must be reduced (Goh and Zhong, 2007b). The demand for reducing manufacturing costs and improving performance is also driving low‐cost packaging for fine pitch and high I/O devices (Shah et al , 2008).…”
Section: The Benefits Of Fine and Ultra‐fine Pitch Wire Bondingmentioning
confidence: 99%
“…Wire bonding using copper wire is a solution to wire sweep because of its high stiffness (Sivakumar et al , 2002), besides other solutions such as using insulated wire (Lyn et al , 2006; Lee, J., et al , 2007b; Lyn and Crockett, 2007; Zhong, 2008b) and having varying loop heights (Zhong et al , 2007a). Compared to gold wire, thinner and longer copper wires can be used for finer pitch packages because of its higher mechanical strength (Shah et al , 2008).…”
Section: Challenges In Fine and Ultra‐fine Pitch Wire Bondingmentioning
confidence: 99%
“…Having a large process window is crucial for stable Cu processing, as it ensures optimal quality production, process portability, and stability [ 10 ]. Studies have shown that the hardness of Cu wire decreases with increasing purity levels [ 11 ]. Hence, using high-purity Cu wire in the bonding process can alleviate damage to the bonding pad caused by Cu wire.…”
Section: Introductionmentioning
confidence: 99%
“…Several different approaches have been explored to reduce underpad stress: Softer wire, producing softer FABs, optimizing the bonding parameters, and modifying the bond pad design are used to limit underpad damage [1,8,9]. Cu bonded ball [9] and Cu FABs [10] with different hardness can be obtained by changing EFO parameters and temperature of the shielding gas.…”
Section: Introductionmentioning
confidence: 99%